Relationships between job satisfaction, occupational burnout and rationing of care among intensive care unit nurses - Tomaszewska, Katarzyna; Kowalczuk, Krystyna; Majchrowicz, Bożena (Frontiers in Public Health, 2024)
Introduction Rationing of nursing care is referred to as overlooking aspects of required patient care. Its result is incomplete or delayed services provided to the patient. Anesthesia nurses employed in an intensive care unit are exposed to a significant workload. Particularly heavy is the psychological burden leading in many cases to the onset of burnout syndrome and a decrease in job satisfaction. The aim of this paper Was to determine the relationship between occupational burnout, job satisfaction and rationing of care among anesthesia nurses employed in intensive care units. Materials and methods The study group consisted of 477 anesthesia nurses employed in intensive care units in Poland. The study was conducted between December 2022 and January 2023. The research tools were BERNCA-R questionnaire, Job Satisfaction Scale questionnaire and Maslach Burnout Inventory questionnaire, which were distributed to selected hospitals with a request to be forwarded to intensive care units and completed. In the statistical analysis, correlations were calculated using Spearman’s rho coefficient, reporting the intensity of the relationship and its positive or negative direction. The analysis was performed using the IBM SPSS 26.0 package with the Exact Tests module. Results The mean score of the BERNCA questionnaire was 1.65 ± 0.82. The mean score of occupational burnout was 60.82 ± 10.46. The level of emotional exhaustion, which significantly affects occupational burnout, was 26.39 ± 6.07, depersonalization was 14.14 ± 3.21 and lack of personal achievement was 20.29 ± 4.70. All the scores obtained exceeded the threshold of 50% of total points, which indicates the presence of occupational burnout at a significant level. The job satisfaction of the nurses surveyed was above mean at 23.00 ± 5.2 out of 35 total points. Conclusion The results proved that there is a statistically significant, although with a weak strength of association, correlation between occupational burnout and rationing of care by anesthesia nurses. As the limitation of anesthesia nurses’ ability to perform certain activities increases, their job satisfaction decreases. In a work environment that is conducive to nurses, there are fewer job responsibilities that are unfulfilled. Therefore, it is essential to create a friendly work environment for nursing staff that will promote the provision of services at the highest possible level.